High-Dose Methotrexate for the Treatment of Relapsed Central Nervous System Erdheim-Chester Disease - Prahlad Ho; Carole Smith (Case Reports in Hematology)
Erdheim-Chester disease (ECD) is a rare multisystem non-Langerhans histiocytosis. CNS involvement is a major complication, which is often rapidly progressive and confers a poor prognosis. However, treatment of CNS ECD is difficult due to poor CNS penetrance by the most effective chemotherapeutic drugs commonly used in this disorder (e.g., interferon and cladribine). We describe a case of a 60-year-old lady with a 5-year history of stable systemic ECD who presented with new brainstem lesions and rapid, steroid-refractory neurological deterioration which required immediate intervention. High-dose methotrexate was chosen due to its rapid onset of action and excellent CNS penetration. Her neurological deterioration was quickly arrested with significant functional improvement, which was sustained for 4 months with consolidation doses of high-dose methotrexate. Subsequent treatment with cladribine and interferon did not confer any appreciable clinical improvement. High-dose methotrexate is effective in controlling rapidly progressive CNS ECD and should be considered as a salvage agent prior to commencement of more definitive treatment.